Good Outcome for an Individual with Severe Facial Anomalies and Hypogonadotropic Hypogonadism: A Consequence of His Cognitive Function, Pragmatic Approach, and Temperament - Timothy L. Groh; William Zarella; Peter A. Lee (Case Reports in Pediatrics)
The multiple factors that determine outcomes for individuals with visible developmental errors and/or atypical development of the reproductive system are not fully understood. This case report of an individual with Bosma arhinia microphthalmia syndrome causing severe facial anomalies and hypogonadotropic hypogonadism is used to highlight factors that impacted his adjustment from childhood through adulthood. Key factors include his temperament, intact cognitive ability, and pragmatic approach for controlling his physical and social environment. His successful adjustment even in the face of significant early life challenges demonstrates that positive outcomes are attainable for individuals with significant developmental errors. His story and experiences with the health-care system offer insight into some factors that may be pertinent to resilience and lifelong adjustment for patients with similar conditions and the importance of continually seeking the patient’s perspective to tailor treatment across the lifespan.